Gran turismo [videorecording (Blu-Ray)] - Hall, Jason, 1972-; Baylin, Zach, 1980-; Tse, Alex; Balfe, Lorne; Kawczynski, Andrew; Parker, Colby, Jr; Jouffret, Jacques; Harbour, David, 1975-; Bloom, Orlando, 1977-; Madekwe, Archie, 1995-; Hira, Takehiro, 1974-; Barnet, Darren, 1991-; et al. (Sony Pictures Home Entertainment, 2023)
Based on the unbelievable true story of a team of unlikely underdogs, a struggling working-class gamer, a failed former racecar driver, and an idealistic motorsport executive. Together, they risk it all to take on the most elite sport in the world. It is an inspiring, thrilling, and action-packed story that proves that nothing is impossible when you're fueled from within.